The Influence of Professional Competencies on Sulh Officers' Performance in Managing Mediation Sessions: Analysis of Skills, Knowledge and Personality Trait - Hajar Ismail, Siti; Abdul Manap, Norhoneydayatie; Md Nasir, Nor Ashikin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Competence is an important attribute for sulh officers in facilitating successful mediation sessions. The failure of such sessions is often linked to a lack of competence among officers, highlighting the need to identify and understand the specific competencies required. This study aims to analyze the essential competencies that sulh officers must possess to effectively conduct mediation. Employing a qualitative research design, data were collected through semi-structured interviews with active sulh officers and analyzed thematically. The findings reveal that facilitation skills, particularly proficiency in language use and body language are fundamental to the success of the sulh process. Additionally, knowledge on legal frameworks and Islamic legislation is also crucial. In addition, personal attributes such as patience, impartiality, and gentleness also play a significant role in mediation effectiveness. On the other point of view, marital status and academic qualifications were found to have no impact on mediation outcomes. The study also underscores the importance of continuous professional development through courses, seminars, and workshops to enhance the competencies of sulh officers. These insights can inform training programs and policy development aimed at strengthening the sulh mechanism